Divergent roles for Clusterin in Lung Injury and Repair. Issue 1 (December 2017) - Habiel, David; Camelo, Ana; Espindola, Milena; Burwell, Timothy; Hanna, Richard; Miranda, Elena; Carruthers, Alan; Bell, Matthew; Coelho, Ana; Liu, Hao; Pilataxi, Fernanda; Clarke, Lori; et al.
Abstract Lung fibrosis is an unabated wound healing response characterized by the loss and aberrant function of lung epithelial cells. Herein, we report that extracellular Clusterin promoted epithelial cell apoptosis whereas intracellular Clusterin maintained epithelium viability during lung repair. Unlike normal and COPD lungs, IPF lungs were characterized by significantly increased extracellular Clusterin whereas the inverse was evident for intracellular Clusterin.In vitro andin vivo studies demonstrated that extracellular Clusterin promoted epithelial cell apoptosis while intercellular Clusterin modulated the expression of the DNA repair proteins, MSH2, MSH6, OGG1 and BRCA1. The fibrotic response in Clusterin deficient (CLU−/− ) mice persisted after bleomycin and it was associated with increased DNA damage, reduced DNA repair responses, and elevated cellular senescence. Remarkably, this pattern mirrored that observed in IPF lung tissues. Together, our results show that cellular localization of Clusterin leads to divergent effects on epithelial cell regeneration and lung repair during fibrosis.